SEGMENTATION OF OBJECTS ON BIOMEDICAL IMAGES USING LIBRARIES OF TEMPLATES - M. M. Alilou; M. V. Sprindzuk (Informatika)
The purpose of this paper is to introduce a robust framework to facilitate simultaneous detection and segmentation of objects with arbitrary size and shape on different kinds of medical images using a library of arbitrary irregular smooth shapes.